Empirical nexus between financial inclusion and carbon emissions: Evidence from heterogeneous financial economies and regions - Shahzad Hussain; Raazia Gul; Sabeeh Ullah; Abdul Waheed; Muhammad Naeem (Heliyon, 2023)
We aim to investigate the empirical nexus between carbon emissions and financial inclusion for a panel of 74 countries from 2004 to 2020 based on the environment kuznets curve (EKC). Using the advanced panel data analysis framework of Driscoll–Kraay, Generalised linear model, and Prais-Winsten test for the entire sample and heterogeneous subsamples, we document an inverted U-shape relationship between carbon emissions and inclusive financial system. Notably, an inverted U-shape relationship is established in developed, emerging and frontier economies except in standalone economies. Furthermore, the analysis of region-wise subsamples reveals that nonlinear relationship varies across regions. The heterogeneous response of financial inclusion in curtailing environmental degradation provides vital policy insights. It suggests that financial inclusion can be used as a mitigation measure based on well-structured and robust regulatory and legal frameworks. These frameworks would create synergy effects of financial inclusion in designing policies and addressing issues related to sustainable development and climate change.